Environmental Factors Shaping the Soil Microbiome - Sa, Tongmin; Anandham, Rangasamy (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book emphasizes that soil productivity is considered an important factor for the success of agricultural production. The microbial community's composition and the diversity of agricultural soils primarily depend on management practices. Exogenous nutritional inputs are inevitable processes in crop production, which can change the structure of soil bacterial communities. The combined application of compost and inorganic fertilizers might be a good way to keep up with agricultural productivity while maintaining the environmental balance. Bacterial communities are also known to differ according to the plant genotypes and hosts. Plant genotypic differences do not always lead to significant differences in microbiomes in the rhizosphere. It was concluded that imaginative research should address the simulation of the soil microenvironment, so as to understand the factors that regulate microbial activities in micro-niches.